2000
DOI: 10.1111/1467-9481.00130
|View full text |Cite
|
Sign up to set email alerts
|

The voices people read: Orthography and the representation of non‐standard speech

Abstract: Combining features of matched guise tests with sociolinguistic interviewing and oral performance, this study investigates the social meanings carried by nonstandard orthographies. Participant evaluations of the personas represented by non-standard orthographies showed that people connected orthography to social identities. Speci®cally, we found that people uncritically and spontaneously read non-standard orthographies as indices of low socioeconomic status. When we asked participants to read texts out loud, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 10 publications
0
29
0
4
Order By: Relevance
“…To control as much as possible for differences of meaning, the two versions of the text presented are matched in their content. Studies using the MGT have shown that speakers using communication conventions of a higher status social group were assumed to have more favorable qualities overall (Giles, 1970;Giles, Williams, Mackie, & Rosselli, 1995;Jaffe & Walton, 2000;Segrest Purkiss, Perrew e, Gillespie, Mayes, & Ferris, 2006;Tsalikis, Ortiz-Buonafina, & LaTour, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…To control as much as possible for differences of meaning, the two versions of the text presented are matched in their content. Studies using the MGT have shown that speakers using communication conventions of a higher status social group were assumed to have more favorable qualities overall (Giles, 1970;Giles, Williams, Mackie, & Rosselli, 1995;Jaffe & Walton, 2000;Segrest Purkiss, Perrew e, Gillespie, Mayes, & Ferris, 2006;Tsalikis, Ortiz-Buonafina, & LaTour, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Existe una especificidad baja y, por lo tanto, son aspectos poco significativos en comparación con estudios previos de escritura con SMS (Jaffe y Walton, 2000;Cassany, 2003;Bodomo y Lee, 2004;Betti, 2006), los siguientes:…”
Section: Caracterización Y Variación Ortotipográfica De La Escritura unclassified
“…Critical discourse analysts suggest that this ignores the influence of society and ideology (Billig 1999a(Billig , 1999bvan Dijk 1999). Ignoring this, some argue, could work to misrepresent participants, their stories, and therefore the rigor of the interpretations made from the transcript (Jaffe and Walton 2000;Preston 1982). …”
Section: Constraints and Opportunities In Transcriptionmentioning
confidence: 99%
“…A hierarchy is implied with standard, American English placed above those that deviate from this norm. Jaffe and Walton (2000) further noted that when these non-standard orthographies are read, they often denote race and class that can then be attached to prejudiced assumptions and analyses. As we mentioned earlier, this happened in our own research when committee members began to associate ethnic and class identities with certain social characteristics (e.g., internalized homophobia and lack of HIV/AIDS awareness).…”
Section: Constraints and Opportunities In Transcriptionmentioning
confidence: 99%